The role of the rhythm step on pro-agility test performance in division I football players - Papadopoulos, P.; Lund, R. J.; Ficklin, T. K.; Reed, J. P. (Research Quarterly for Exercise and Sport, 2021)
Purpose: The pro-agility test is a common test in multiple sports. A common way to start is the crossover step (CS) where athletes start the drill by crossing one leg over the other. However, the rhythm step (RS), initiated by moving one foot medially before crossing the opposite foot over the first, may result in faster time. Therefore, the purpose of this study was to compare the RS to the CS in the pro-agility test.